Analyse des risques microbiens du lait cru local à Abidjan (Côte d’Ivoire) - Kouamé-Sina, S.M.; Bassa, A.; Dadie, A.; Makita, K.; Grace, Delia; Dje, M.; Bonfoh, Bassirou (2010)
The hygiene practices during milking, the microbiological and chemical quality of cow raw milk from production to sale were studied in 15 small dairies in Abidjan. The analysis of raw milk quality showed that 81.5% of raw milk taken udders of cow were of good quality, against 35.30% for raw milk on sale. The average of Coliforms was 8.7.103 cfu/ml for raw milk taken cow’s udder, 3.2.105 cfu/ml for raw milk in tank and 9.9.105 cfu/ml for raw milk sales. The udders of cows, hands of milkers were identified as primary sources of milk contamination. The utensils (farmer, vendor) and environment were identified as major sources of secondary contamination. In addition, 24.7% of milk contained antibiotics and 50% of raw milk on sale were wet with water. The occurrence of food borne diseases is significantly related to the behavior of consumption of unpasteurized raw milk (P<0.05) with a relative risk of 2.81 (95%CI: 1.17 – 6.78). The zootechnical management of actors and popularization of good hygiene practices throughout the production chain are necessary for improvement of local milk quality.